Issues and challenges of forensics analysis of agents' behavior in multi-Agent systems: A critical review - Musa N.A.; Yusoff M.Z.M.; Ismail R.; Yusoff Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer forensics; Robotics; Agent behavior; Critical analysis; Forensic analysis; Forensics analysis; Issues and challenges; Monitoring agents; Multi agent; Multi-agents systems; Multi agent systems